2001
DOI: 10.1016/s0736-0266(00)00073-5
|View full text |Cite
|
Sign up to set email alerts
|

Injuries produced by blunt trauma to the human patellofemoral joint vary with flexion angle of the knee

Abstract: Patellofemoral joint impact trauma during car accidents, sporting activities, and falls can produce acute gross fracture of bone, microfracture of bone, and soft tissue injury. Field studies of car accidents, however, show that most patellofemoral traumas are classified as 'subfracture' level injuries. While experimental studies have shown that the influence of flexion angle at impact is not well understood, flexion anglc may influence injury location and severity. In the current study, 18 pairs of isolated hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Donzelli et al also found that changing the curvature of the articular layers influences the patterns of stress distribution, a phenomenon that was not investigated in the current study. In a clinical context it is of importance to note that experimental studies of the impact response of articular cartilage [60,61] have demonstrated that fissures may appear both at the articular surface and at the cartilage-bone interface. This suggests that fissures at the articular surface may occur due to excessive tensile stresses, shear stresses, or strain-energy density, while failure at the cartilage-bone interface may occur due to excessive normal or shear strains [17,62].…”
Section: Discussionmentioning
confidence: 99%
“…Donzelli et al also found that changing the curvature of the articular layers influences the patterns of stress distribution, a phenomenon that was not investigated in the current study. In a clinical context it is of importance to note that experimental studies of the impact response of articular cartilage [60,61] have demonstrated that fissures may appear both at the articular surface and at the cartilage-bone interface. This suggests that fissures at the articular surface may occur due to excessive tensile stresses, shear stresses, or strain-energy density, while failure at the cartilage-bone interface may occur due to excessive normal or shear strains [17,62].…”
Section: Discussionmentioning
confidence: 99%
“…The strain distribution across the articular layers under such physiological load magnitudes has not been well described; thus it is unclear whether cartilage strains are on the order of ∼10% or ∼50%, or some other representative value, for normal activities of daily living. Furthermore, it is uncertain whether the greatest strain magnitudes occur near the articular surface or near the cartilage-bone interface; under impact loading, failure of cartilage has been reported at both locations (Atkinson and Haut, 1995; Atkinson and Haut, 2001b; Haut et al, 1995; Thompson et al, 1993). …”
Section: Introductionmentioning
confidence: 99%
“…Research on the effect of impact loading on the knee joint includes only a few major categories; e.g., local injury mechanics (Radin et al, 1973;Repo and Finlay, 1977;Torzilli et al, 1999;Zhang et al, 1999) and biomechanics of components, such as articular cartilage or subchondral bone, the biological response of lower extremity due to blunt impact loading (Atkinson et al, 2001;Atkinson and Haut, 1995;Atkinson and Haut, 2001a;Atkinson and Haut, 2001b;Donohue et al, 1983;Hurwitz, 1984;Thompson et al, 1991), and global biomechanics such as kinematics and kinetics of total knee joint during impact loading (Chu et al, 1986;Hoshino and Wallace, 1987). Although there are many knee injury studies, how external devices or strategies can help to minimize knee injury from external impact loading has still not been addressed.…”
Section: Introductionmentioning
confidence: 99%